Factors Supporting an Information Technology Management : Teachers in Primary Schools in Thailand - Daoprakai Raso; Pariyaporn Tungkunanan; Abhichat Anukulwech (My University, 2017)
The objectives of this research were (1) to study the authentic situation of the Information Technology Management of Teachers in Primary Schools in Thailand (2) to study the factors supporting the Information Technology Management of Teachers in Primary Schools in Thailand .
The sample group consisted of 165 teachers, teaching in primary schools under the office of the basic education commission (OBEC) in Thailand in 2016. By using multi-stage sampling technique. Data were collected by using questionnaire include 101 questions from 6 factors in which the questionnaires were approved content validity from experts at level of 0.95 and 0.97, respectively. The statistics were used to analyse the data as follows: mean (M), standard deviation (S.D),and Stepwise Multiple Regression Analysis. The study revealed that (1) the authentic situation of the Information Technology Management was found at “very often” level for the operation of the information technology management x ̅ = 4.09 and S.D.= 0.47 and (2) the factors that support the Information Technology Management consisting of the hardware factors and the people factor. The percentage was 28.80 and 32.70 consecutively, and shown the raw score and standard score was found from this formula Ý = 1.989 + .322(X1) + .178(X6) Ź = .363(X1) + .262(X6).
Keywords: Raw score; Stepwise regression; Sample (material); Technology-Enhanced Education Studies